11 - Domination and Resistance through the Prism of Postage Stamps - Agbenyega Adedze, (Afrika Zamani, 2022)
Every country issues postage stamps. Stamps were originally construed as pre- payment for the service of transporting letters and packages. However, images on stamps have become mediums for the transmission of propagandist messages about the country of issue to its citizens and the rest of the world. Commemorative postage stamps venerate special events, occasions or personalities and are, therefore, subject to political and social pressure from special interest groups. It is not, therefore, surprising that during the colonial era, Europeans memorialized conquerors and explorers on postage stamps and, likewise after independence, African countries have commemorated some of their leaders (freedom fighters, martyrs, politicians, chiefs, etc.) who resisted colonial rule. Using postage stamps of British and French colonies and six independent countries (Benin, Côte d’Ivoire, Ghana, Guinea, Nigeria and Senegal) in West Africa, I will try to explain why certain individuals are honored and why others are not. I argue that since the issuing of postage stamps remains the monopoly of the central government, these commemorative stamps about domination and resistance are subjective and are found to be interpreted through contemporary political prism. Recent democratic dispensation in Africa has also influenced commemorative stamps to a large extent. Under these conditions, public history debates are now possible where people could claim their own history, and I predict that as more constituents realize the value of postage stamps, marginalized groups will demand stamps for their heroes and heroines.